Mecanismos de governança corporativa na pequena empresa familiar - Marchi, Diego de (2014)
This thesis aims to describe and analyze how the phenomenon of corporate governance articulates management mechanisms and impacts the dynamics of a small family organization. For this, we used the perspectives of Fan (2001) and Silva Junior (2006), dealin